Epigallocatechin Gallate Modulates Essential Elements, Zn/Cu Ratio, Hazardous Metal, Lipid Peroxidation, and Antioxidant Activity in the Brain Cortex during Cerebral Ischemia - Ming-Cheng Lin; Chien-Chi Liu; Yu-Chen Lin; Ching-Wen Hsu (MDPI AG, 2022)
Cerebral ischemia induces oxidative brain injury via increased oxidative stress. Epigallocatechin gallate (EGCG) exerts anti-oxidant, anti-inflammatory, and metal chelation effects through its active polyphenol constituent. This study investigates whether EGCG protection against cerebral ischemia-induced brain cortex injury occurs through modulating lipid peroxidation, antioxidant activity, the essential elements of selenium (Se), zinc (Zn), magnesium (Mg), copper (Cu), iron (Fe), and copper (Cu), Zn/Cu ratio, and the hazardous metal lead (Pb). Experimentally, assessment of the ligation group was performed by occlusion of the right common carotid artery and the right middle cerebral artery for 1 h. The prevention group was intraperitoneally injected with EGCG (50 mg/kg) once daily for 10 days before cerebral ischemia. The brain cortex tissues were homogenized and the supernatants were harvested for biochemical analysis. Results indicated that cerebral ischemia markedly decreased SOD, CAT, Mg, Zn, Se, and Zn/Cu ratio and increased malondialdehyde (MDA), Fe, Cu, and Pb in the ischemic brain cortex. Notably, pretreating rats with EGCG before ischemic injury significantly reversed these biochemical results. Our findings suggest that the neuroprotection of EGCG in the ischemic brain cortex during cerebral ischemia involves attenuating oxidative injury. Notably, this neuroprotective mechanism is associated with regulating lipid peroxidation, antioxidant activity, essential elements, Zn/Cu ratio, and hazardous metal Pb.